Systemic Therapy for Youth at Clinical High Risk for Psychosis: A Pilot Study - Shi, Jingyu; Wang, Lu; Yao, Yuhong; Zhan, Chenyu; Su, Na; Zhao, Xudong (Frontiers in Psychiatry, 2017)
Psychosocial intervention trials for youth at clinical high risk (CHR) for psychosis have shown promising effects on treating psychotic symptoms but have not focused on psychosocial functional outcomes, and those studies have been conducted among help-seeking patients; there is a lack of research on non-clinical young CHR individuals. Systemic therapy (ST) is grounded in systemic-constructivist and psychosocial resilience theories. It has a number of advantages that makes it attractive for use with CHR individuals in non-clinical context. The present study evaluated the effect of ST for students at CHR on reducing symptoms and enhancing psychosocial function. This was a single-blind randomized controlled trial for CHR young people comparing ST to supportive therapy with a 6-month treatment. Psychotic and depressive symptoms (DS) as well as self-esteem and social support (SS) were assessed at pre- and posttreatment. 26 CHR individuals were randomly divided into intervention group (n = 13) and control group (n = 13). There were no significant differences in severity of symptoms, level of SS and self-esteem at baseline between the two groups (P > 0.05). At posttreatment, significant improvements in positive and DS as well as SS and self-esteem were observed in the ST group (P < 0.05); in the control group, these improvements were not significant (P > 0.05). The findings indicated that systemic intervention for university students at CHR for psychosis may have a positive effect on symptoms and self-esteem as well as SS in short term. More long-term research is needed to further evaluate this intervention.